Revitalization of the Sakinah Family in Weru Village: Women's Empowerment and Child Protection Based on Asset-Based Community Development (ABCD) - Mazroatus Saadah; Umi Chaidaroh; Dimyati (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Background: This community engagement program addresses the challenge of strengthening family resilience (sakinah families) by focusing on women's empowerment and child protection within the community. The program utilizes an asset-based perspective to build upon existing community strengths rather than focusing solely on deficiencies. Purpose of the Study: The program aims to revitalize the function of sakinah families through the specific objectives of enhancing women's leadership, providing Islamic parenting education, preventing early marriage, and fostering economic empowerment. Methods: The program was implemented using the Asset-Based Community Development (ABCD) framework, structured into five key stages: discovery, dream, design, delivery, and destiny. Activities included educational workshops, forum establishment, and productive economic training. Results: Quantitative results showed a significant increase in participants' legal and religious literacy, with understanding of the legal minimum marriage age rising from 36% to 89%. The program successfully established a sustainable women's forum (20 leaders) that coordinates monthly parenting and adolescent counseling sessions. Furthermore, the formation of a women's business group led to an average 15% increase in household income, demonstrating enhanced economic agency. The ABCD approach proved effective in building sustainable community structures for family development.